Increasing Spiritual Intelligence Through the Implementation of Science-Based Learning in Early Childhood - Lita, Lita; Gilar Jatisunda, Mohamad; Riepah, Ipah; Hidayanti, Maria; Rosidah, Ani (Departement of PAI, Universitas Majalengka, 2024)
The aim of this study was to investigate the effect of science-based learning on improving mental intelligence in early childhood. A quasi-experimental method was used with two groups, an experimental group that participated in science-based learning and a control group that did not participate in the intervention. Data was collected by pre-testing and post-testing spiritual intelligence in both groups. The results showed that there was no significant difference in the mean pretest score between the two groups. However, after undergoing science-based learning, the experimental group showed a significant increase in the mean posttest score of spiritual intelligence compared to the control group. These findings suggest that science-based learning has the potential to enhance spiritual intelligence in early childhood. Therefore, it is recommended that educators and parents use this approach in early childhood education to strengthen the spiritual intelligence aspect. Although this study has limitations, the results provide insight into the relationship between science-based learning and the development of spiritual intelligence in early childhood.